2022
DOI: 10.3390/polym14010201
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Rigid Polyurethane Foam from Wasted Palm Oil and Water Hyacinth Fiber Composite—A Green Sound-Absorbing Material

Abstract: A novel rigid sound-absorbing material made from used palm oil-based polyurethane foam (PUF) and water hyacinth fiber (WHF) composite was developed in this research. The NCO index was set at 100, while the WHF content was set at 1%wt with mesh sizes ranging from 80 to 20. The mechanical properties, the morphology, the flammability, and the sound absorption coefficient (SAC) of the PUF composite were all investigated. When the WHF size was reduced from 80 to 20, the compression strength of the PUF increased fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…The acid number for free acid in UPO and residual acid after the reaction in MUPO rose slightly from 1.41 to 1.76 mgKOH/g. These findings suggested that UPO is effectively changed by oxidation and hydroxylation to mUPO, which corresponded to the previous works [ 27 , 28 , 29 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The acid number for free acid in UPO and residual acid after the reaction in MUPO rose slightly from 1.41 to 1.76 mgKOH/g. These findings suggested that UPO is effectively changed by oxidation and hydroxylation to mUPO, which corresponded to the previous works [ 27 , 28 , 29 ].…”
Section: Resultssupporting
confidence: 92%
“…The chemical structure confirmation of UPO and mUPO has been reported in our previous work [ 27 , 28 , 29 , 30 ]. The figure of 1 H-NMR spectra and FTIR spectra is presented in Figures S1 and S2 , respectively.…”
Section: Methodssupporting
confidence: 73%
“…From Figure 4 a–d, it can be explained that peaks at 2992.98 cm −1 , 2929.34 cm −1 , 2923.55 cm −1 and 2920.14 cm −1 can be attributed to the C–H stretching from alkane groups. The C=O peaks, the carbonyl groups or carboxylate ( Tran et al., 2021 ), with values of 1625.69 cm −1 , 1637.26 cm −1 , 1654.62 cm −1 , and 1651.73 cm −1 , respectively ( Sukhawipat et al., 2021 ), exist in water lettuce (mixed) and water hyacinth (mixed and non-mixed). Tran et al.…”
Section: Resultsmentioning
confidence: 99%
“…(2017) stated that –OH hydroxyl groups can be found widely in the golden shower fruits, ranging from 3409 to 3417 cm −1 . The existence of –OH groups ranging from 3300 to 3500 cm −1 ( Sukhawipat et al., 2021 ). Tran et al.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, the mUPO was further analyzed for its iodine value, acid value and hydroxyl value. The chemical structure con rmation of UPO and mUPO has been reported in our previous work [23][24][25][26].…”
Section: Methodsmentioning
confidence: 95%